Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

A massive ingression of the alien species Mytilus edulis L. (Bivalvia: Mollusca) into the Mediterranean Sea following the Costa Concordia cruise-ship disaster - E. CASOLI; D. VENTURA; M. V. MODICA; A. BELLUSCIO; M. CAPELLO; M. OLIVERIO; G. ARDIZZONE (Mediterranean Marine Science, 2016)
The Costa Concordia cruise-ship disaster occurred just off the coast of Italy on January 13th, 2012, and entailed the largest marine salvage operation in history. The salvage employed vessels from different European harbours, providing an unexpected means for transporting alien species into the Mediterranean. In this work we identified mussel species using fragments length polymorphism of a nuclear locus and report the first evidence of the transport of the blue mussel, Mytilus edulis Linnaeus, 1758 (Bivalvia: Mollusca), into the Mediterranean Sea, as a part of the fouling community of the hull of an accommodation barge arrived from a NE Atlantic location in October 2012. Furthermore, we describe the rapid growth of this species, under the ASV Pioneer, until its almost total extinction during the summer of 2013, which left a covering of mussel shells on the underlying Posidonia oceanica (Linnaeus) Delile, 1813. meadow. This high mortality rate indicated that M. edulis had been exposed to high stress conditions, probably due to different salinity, temperature, and oligotrophic conditions from its place of origin, and there was no spawning event or known settlement on the nearest infralittoral natural habitats. This event reminds us of how the Mediterranean Sea is constantly under alien-species pressure, due to human activities.

First record of Calma gobioophaga Calado and Urgorri, 2002 (Gastropoda: Nudibranchia) in the Mediterranean Sea - J. PRKIC; G. FURFARO; P. MARIOTTINI; L. CARMONA; J. L. CERVERA; M. V. MODICA; M. OLIVERIO (Mediterranean Marine Science, 2014)
Specimens of the nudibranch genus Calma were observed under stones at two Croatian localities while feeding on gobiid eggs. Some ambiguous morphological features compared with the original descriptions of the known species of the genus, C. glaucoides and C. gobioophaga, hampered an easy identification. Genetic data (COI and 16S sequences) confirmed the distinction between the two species of the genus Calma, and allowed to unambiguously identify the Croatian specimens as Calma gobioophaga. This is the first record of this species for the Mediterranean and extends remarkably its distribution range. Finally, the eggs fed by the Croatian specimens have been taxonomically identified by using the 12S rDNA marker as Gobius cobitis.

Large‐scale species delimitation method for hyperdiverse groups - N. PUILLANDRE; M. V. MODICA; Y. ZHANG; L. SIROVICH; M.‐C. BOISSELIER; C. CRUAUD; M. HOLFORD; S. SAMADI (Molecular Ecology, 2012)
Accelerating the description of biodiversity is a major challenge as extinction rates increase. Integrative taxonomy combining molecular, morphological, ecological and geographical data is seen as the best route to reliably identify species. Classic molluscan taxonomic methodology proposes primary species hypotheses (PSHs) based on shell morphology. However, in hyperdiverse groups, such as the molluscan family Turridae, where most of the species remain unknown and for which homoplasy and plasticity of morphological characters is common, shell‐based PSHs can be arduous. A four‐pronged approach was employed to generate robust species hypotheses of a 1000 specimen South‐West Pacific Turridae data set in which: (i) analysis of COI DNA Barcode gene is coupled with (ii) species delimitation tools GMYC (General Mixed Yule Coalescence Method) and ABGD (Automatic Barcode Gap Discovery) to propose PSHs that are then (iii) visualized using Klee diagrams and (iv) evaluated with additional evidence, such as nuclear gene rRNA 28S, morphological characters, geographical and bathymetrical distribution to determine conclusive secondary species hypotheses (SSHs). The integrative taxonomy approach applied identified 87 Turridae species, more than doubling the amount previously known in the Gemmula genus. In contrast to a predominantly shell‐based morphological approach, which over the last 30 years proposed only 13 new species names for the Turridae genus Gemmula , the integrative approach described here identified 27 novel species hypotheses not linked to available species names in the literature. The formalized strategy applied here outlines an effective and reproducible protocol for large‐scale species delimitation of hyperdiverse groups.